On the influence of poleward jet shift on shortwave cloud feedback in global climate models. (30th December 2015) - Wall, Casey J.; Hartmann, Dennis L.
Abstract: Experiments designed to separate the effect of atmospheric warming from the effect of shifts of the eddy‐driven jet on shortwave (SW) cloud feedback are performed with three global climate models (GCMs). In each model a warming simulation produces a robust SW cloud feedback dipole, with a negative (positive) feedback in the high‐latitudes (subtropics). The cloud brightening in high‐latitudes that characterizes warming simulations is not produced by jet shifts alone in any of the models, but is highly sensitive to perturbations of freezing temperature seen by the cloud microphysics scheme, indicating that thermodynamic mechanisms involving the phase of cloud condensate dominate the SW feedback at high‐latitudes. In one of the models a poleward jet shift causes significant cloud dimming throughout the midlatitudes, but in two models it does not. Differences in cloud response to jet shifts in two of the models are attributed to differences in the shallow convection parameterizations. Key Points: High‐latitude shortwave cloud feedback in GCMs driven by cloud microphysics, not jet shifts Inter‐model differences in low cloud response to jet shift linked to shallow convection